The HD-GYP domain protein RpfG of Xanthomonas oryzae pv. oryzicola regulates synthesis of extracellular polysaccharides that contribute to biofilm formation and virulence on rice. - Yuanbao Zhang; Chao Wei; Wendi Jiang; Lei Wang; Churui Li; Yunyue Wang; John Maxwell Dow; Wenxian Sun (PLoS ONE, 2013)
Bacterial leaf streak caused by Xanthomonas oryzae pv. oryzicola (Xoc) is one of the most important diseases in rice. However, little is known about the pathogenicity mechanisms of Xoc. Here we have investigated the function of three HD-GYP domain regulatory proteins in biofilm formation, the synthesis of virulence factors and virulence of Xoc. Deletion of rpfG resulted in altered production of extracellular polysaccharides (EPS), abolished virulence on rice and enhanced biofilm formation, but had little effect on the secretion of proteases and motility. In contrast, mutational analysis showed that the other two HD-GYP domain proteins had no effect on virulence factor synthesis and tested phenotypes. Mutation of rpfG led to up-regulation of the type III secretion system and altered expression of three putative glycosyltransferase genes gumD, pgaC and xagB, which are part of operons directing the synthesis of different extracellular polysaccharides. The pgaABCD and xagABCD operons were greatly up-regulated in the Xoc ΔrpfG mutant, whereas the expression of the gum genes was unaltered or slightly enhanced. The elevated biofilm formation of the Xoc ΔrpfG mutant was dramatically reduced upon deletion of gumD, xagA and xagB, but not when pgaA and pgaC were deleted. Interestingly, only the ΔgumD mutant, among these single gene mutants, exhibits multiple phenotype alterations including reduced biofilm and EPS production and attenuated virulence on rice. These data indicate that RpfG is a global regulator that controls biofilm formation, EPS production and bacterial virulence in Xoc and that both gumD- and xagB-dependent EPS contribute to biofilm formation under different conditions.